Therapeutic support protocol for patient with dysosmia with or without dysgeusia related to the SARS-CoV2 virus infection - Milone, Ignazio; Vento, Riccardo; Ippolito, Luigi; Paroni, Samuel; Vento , Maurizio Giuseppe (Acta Biomedica Atenei Parmensis, 2020)
.